High-voltage low-loss dielectric material and preparation method thereof

Through composite materials and doping modification, the dielectric materials of high-voltage ceramic capacitors are optimized, which solves the problems of low dielectric constant, large loss and poor stability, and achieves efficient and stable dielectric performance, which is suitable for high-frequency and high-electric field environments.

CN120535306AActive Publication Date: 2025-08-26KUNSHAN QINGYUAN ELECTRONIC TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510723294.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-26
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

The dielectric materials of existing high-voltage ceramic capacitors have low dielectric constant, large dielectric loss, poor pressure resistance and high temperature stability, and contain harmful elements. The preparation process is complicated and it is difficult to maintain stable performance under high frequency and high electric fields.

Method used

Composite materials with barium titanate, strontium titanate, bismuth oxide and other components are used to optimize dielectric properties by refining the grains, adjusting the crystal structure and doping modification, and zirconium oxide, cerium oxide, vanadium pentoxide and other components are added to improve the dielectric constant of the material, reduce losses and enhance mechanical properties.

Benefits of technology

It realizes dielectric materials with high dielectric constant, low dielectric loss, high voltage resistance and high temperature stability, and is suitable for high voltage ceramic capacitors, improving the efficiency and reliability of the capacitor.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a high-voltage low-loss dielectric material and a preparation method thereof, and relates to the technical field of high-voltage ceramic capacitors, and the high-voltage low-loss dielectric material comprises the following raw materials in parts by mass: 35-38 parts of barium titanate, 20-29.5 parts of strontium titanate, 15-17.5 parts of titanium dioxide, 9-12 parts of bismuth oxide, 3-4 parts of zirconium oxide, 0.8-1.0 part of X, 1.2-1.4 parts of antimony oxide, 1-1.2 parts of calcium carbonate and the like. The preparation method of the dielectric material comprises the following steps: 1, preparing the dielectric material; melting calcium carbonate, magnesium oxide, zinc oxide and the like, performing water quenching, and performing ball-milling granulation to obtain zinc borosilicate glass powder; uniformly mixing the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide and the like, and granulating to obtain oxide powder; and tabletting and sintering the oxide powder to obtain the high-pressure low-loss dielectric material. The high-voltage low-loss dielectric material is high in dielectric constant, small in dielectric loss, high in compression strength and good in high-temperature stability, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-voltage ceramic capacitors, and in particular to a high-voltage low-loss dielectric material and a preparation method thereof. Background Art

[0002] In modern electronics and power systems, high-voltage ceramic capacitors are widely used in a variety of high-voltage applications, such as high-power electronic devices, power transmission and distribution systems, pulsed power systems, and high-frequency communications, due to their high capacitance density, low equivalent series resistance (ESR), and good temperature stability. Key performance parameters of high-voltage ceramic capacitors are the dielectric constant and dielectric loss of their dielectric material. A high dielectric constant increases the capacitor's capacitance density, while low dielectric loss contributes to improved efficiency and reliability.

[0003] Traditional dielectric materials, such as the widely used barium titanate (BaTiO3)-based ceramics, have long held a prominent position in the electronics industry. These materials are known for their relatively high dielectric constants, making them valuable for applications in electronic components such as capacitors. However, these materials also have some significant drawbacks.

[0004] One of the most significant issues is their relatively high dielectric loss. This means that a significant portion of energy is lost as heat during the storage and conversion process. This not only reduces the overall efficiency of electronic devices but can also lead to heating, unstable performance, and even a shortened lifespan. Barium titanate-based ceramics are particularly susceptible to polarization losses in high-electric-field environments, a phenomenon that further exacerbates energy waste and severely limits the efficiency of capacitors in high-voltage applications.

[0005] In addition to the shortcomings in dielectric properties, the preparation process of barium titanate-based ceramic materials is also quite complicated. The proportions of multiple chemical components and reaction conditions need to be precisely controlled during the production process to ensure the stable performance of the final product. This not only increases production costs, but also makes large-scale production more challenging. At the same time, due to the limitations of the characteristics of the material itself, the performance of barium titanate-based ceramics in high-frequency applications is not ideal, which further limits their widespread application in modern electronic devices. In recent years, researchers have tried to optimize the electrical properties of dielectric materials through doping modification or other physical and chemical methods. For example, by doping rare earth elements or transition metal elements to increase the dielectric constant of the material, and by optimizing the sintering process to reduce the dielectric loss. However, these methods can often only improve the performance of the material to a certain extent, and it is difficult to achieve high dielectric constant and low dielectric loss at the same time.

[0006] Furthermore, existing dielectric materials suffer from poor temperature stability in high-frequency and high-voltage environments. As the operating frequency and power density of electronic devices continue to increase, the performance stability of dielectric materials in high-frequency and high-electric-field environments becomes increasingly important. However, existing high-voltage ceramic capacitor dielectric materials are susceptible to variations in dielectric constant and dielectric loss under these conditions, resulting in unstable capacitor performance.

[0007] The dielectric materials used in the production of high-voltage ceramic capacitors in the prior art contain harmful elements such as lead, which can cause harm to humans and the environment. In addition, the dielectric materials have a low dielectric constant, high dielectric loss, and low DC breakdown voltage. Summary of the Invention

[0008] The present invention provides a high-voltage low-loss dielectric material and a preparation method thereof, in order to solve the technical problems in the prior art of the dielectric material of high-voltage ceramic capacitors, such as low dielectric constant, large dielectric loss, poor withstand voltage strength and high-temperature stability.

[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: A high-voltage low-loss dielectric material, the raw materials of which include 35-38 parts of barium titanate, 20-29.5 parts of strontium titanate, 15-17.5 parts of titanium dioxide, 9-12 parts of bismuth oxide, 3-4 parts of zirconium oxide, X 0.8-1.0 parts, Sb2O3 1.2-1.4 parts, calcium carbonate 1-1.2 parts and / or magnesium oxide 0.13-0.15 parts, wherein X is a mixture of Nb2O5 and Y2O3.

[0010] Preferably, the raw materials further include, by mass, 0.8-0.9 parts of cerium dioxide, 0.08-0.11 parts of manganese dioxide, 0.3-0.4 parts of vanadium pentoxide and / or 0.08-0.1 parts of dysprosium oxide.

[0011] Preferably, the raw materials further include, by mass, 4.7-5.4 parts of zinc oxide, 2.6-3 parts of boric acid, 2.6-3 parts of silicon dioxide, 2-2.4 parts of sodium carbonate and / or 0.09-0.12 parts of aluminum oxide.

[0012] Preferably, the mass ratio of Nb2O5 to Y2O3 in X is 3:7.

[0013] A method for preparing the above-mentioned high-voltage low-loss dielectric material comprises the following steps: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate and / or aluminum oxide are melted, quenched with water, and ball-milled to obtain zinc borosilicate glass powder; S2. Evenly mixing the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide and / or dysprosium oxide, and granulating the mixture to obtain an oxide powder; S3. Pressing the oxide powder into tablets and sintering at 1150° C.-1200° C. to obtain a high-voltage and low-loss dielectric material.

[0014] Preferably, the melting temperature in S1 is 1100-1200° C., and the melting time is 1-1.5 h.

[0015] Preferably, the zinc borosilicate glass powder in S1 has a D50 less than 0.1 μm.

[0016] Preferably, the D50 of the oxide powder in S2 is 0.15-0.5 μm.

[0017] Preferably, the tableting pressure in S3 is 400-500 MPa.

[0018] An application of the high-voltage, low-loss dielectric material described above in a high-voltage ceramic capacitor.

[0019] The present invention incorporates zirconium oxide, cerium dioxide, vanadium pentoxide, manganese dioxide, dysprosium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate, and aluminum oxide to optimize the dielectric constant, dielectric loss, and breakdown voltage of the ceramic material. By refining the grain size, reducing defects, improving thermal stability, and enhancing mechanical properties, the material exhibits excellent overall performance in high-pressure, high-temperature, and high-frequency environments.

[0020] The high-voltage and low-loss dielectric material in the present invention is a doped modified BST ceramic, which belongs to the ABO3 type perovskite structure, wherein the A position and the B position can be replaced, thereby realizing the adjustment of the BST ceramic crystal structure. In the present invention, bismuth oxide is added, and since the ionic radius of Bi is 0.113nm, it is larger than Ba. 2+ (r=0.160nm) and Sr 2+ The radius of Bi (r=0.144nm) is small, and Bi replaces the ions at the A position, which will produce vacancy defects at the A position, thereby increasing the lattice energy, promoting the diffusion and migration of particles during the sintering process, and promoting sintering. 3+ With 6s 2 The electron configuration outside the nucleus is highly polarized.

[0021] Mg 2+ Mg doping at the A site of SrTiO3 refines the grain size of SrTiO3 ceramics and improves the breakdown strength, while having almost no effect on the dielectric constant. This results in SrTiO3 ceramics having good dielectric frequency stability and low dielectric loss at room temperature.

[0022] X is a mixture of Nb2O5 and Y2O3, Nb 5+ and Y 3+ Ion doping can change the lattice structure of the material, promote the mobility of electric domains, introduce relaxation effect, and enable the material to maintain a high dielectric constant and low loss under high-frequency electric fields. The doping of Nb2O5 and Y2O3 can enhance the phase stability of SrTiO3, prevent the material from undergoing phase change at high temperatures, and significantly improve the temperature dependence of SrTiO3, allowing it to maintain a high dielectric constant and low loss over a wide temperature range. In addition, Nb + ions can reduce the formation of large electric domains, and Y 3+ Ions can improve the reversibility of the domain wall. The synergistic effect of the two makes the domain structure more uniform and stable, improves the reversibility of the domain, and thus achieves more efficient polarization reversal under the action of the electric field.

[0023] At the same time, due to the hexacoordinated Y 3+ Ions can replace the A-site ions and B-site ions of SrTiO3 at the same time. 3+ When entering the A position, a vacancy defect will be generated. 3+ The ion radius is small, and the lattice contraction after replacing the A position is strong, which increases the internal stress of the system and improves the dielectric constant of SrTiO3 ceramics. 5+ ) replace part of Ti 4+ , introducing electrons (negative charge) and enhancing the material's polarizability. Niobium doping also promotes liquid-phase sintering, improving sintering efficiency and the material's thermal stability. Ca doping also enhances the interaction between positive and negative ions in SrTiO3 ceramics, increasing their breakdown voltage.

[0024] When Sb2O3 is introduced into the doping system, under the influence of a strong electric field, the electric domains within the ferroelectric ceramic grains align along the direction of the electric field, generating corresponding electrostrain. The magnitude of the stress associated with this strain is proportional to the grain diameter; larger grains are associated with greater stress. Repeated electrostrain can lead to the formation and development of cracks in the grains or at grain boundaries, ultimately causing breakdown of the ceramic material. Sb2O3 doping reduces grain size, thereby reducing the stress associated with electrostrain and improving the compressive strength of the ceramic system.

[0025] Sr, Zr, and Ca are mainly used to dissolve barium titanate, thereby adjusting the Curie temperature; MgO is enriched at the grain boundaries, which plays a role in refining the grains; X and Sb2O3 can be used to form the outer shell of BaTiO3, adjusting the temperature characteristics of the capacitor, reducing losses, and improving insulation through heterovalent combination; glass powder can effectively reduce the sintering temperature, improve density, increase insulation and reduce losses; bismuth oxide as a sintering aid can also reduce the sintering temperature, and due to Bi 3+ The higher ionic polarizability itself increases the dielectric constant.

[0026] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The high-voltage and low-loss dielectric material of the present invention adds bismuth oxide to promote the diffusion and migration of particles during the sintering process, promote sintering, loosen the lattice, and improve Ti 4+ activity, which increases the dielectric constant.

[0027] (2) Mg 2+ By replacing the A site of SrTiO3, Mg doping makes the grain size of SrTiO3 ceramics finer, the interaction between positive and negative ions stronger, and the breakdown strength higher.

[0028] (3) Nb 5+ and Y 3+ The co-doping of ions can change the lattice structure of the material, promote the mobility of the electric domain, introduce the relaxation effect, and enable the material to maintain a high dielectric constant and low dielectric loss under high frequency electric field and wide temperature range; niobium ions (Nb 5+ ) replace part of Ti 4+ , introducing electrons (negative charge), calcium ions (Ca 2+ ) replace part of Ba 2+ or Sr 2+ , introducing holes (positive charges) to achieve overall charge balance and avoid dielectric loss caused by excessive free electrons.

[0029] (4) The high-voltage, low-loss dielectric material of the present invention has a high dielectric constant, low dielectric loss, high compressive strength, and good high-temperature stability. DETAILED DESCRIPTION

[0030] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0031] A high-voltage, low-loss dielectric material, whose raw materials, calculated by mass, include 35 parts of barium titanate, 20 parts of strontium titanate, 15 parts of titanium dioxide, 9 parts of bismuth oxide, 3 parts of zirconium oxide, 0.24 parts of Nb2O5, 0.56 parts of Y2O3, 1.2 parts of Sb2O3, 1 part of calcium carbonate, 0.13 parts of magnesium oxide, 0.8 parts of cerium dioxide, 0.08 parts of manganese dioxide, 0.3 parts of vanadium pentoxide, 0.08 parts of dysprosium oxide, 4.7 parts of zinc oxide, 2.6 parts of boric acid, 2.6 parts of silicon dioxide, 2 parts of sodium carbonate and 0.09 parts of aluminum oxide.

[0032] A method for preparing the high-voltage, low-loss dielectric material described above comprises the following steps: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate, and aluminum oxide are fully mixed, melted at 1100° C. for 1 hour, and then water-quenched. Zinc borosilicate glass powder is obtained by ball milling and granulation, wherein the zinc borosilicate glass powder has a D50 of less than 0.1 μm. S2. Evenly mix the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide, and dysprosium oxide, and granulate to obtain an oxide powder having a D50 of 0.5 μm. S3. Pressing the oxide powder into tablets at a pressure of 400 MPa, and sintering at 1150° C. for 2 h to obtain a high-voltage, low-loss dielectric material. Example 2

[0033] A high-voltage, low-loss dielectric material comprises raw materials, calculated by mass, including 38 parts of barium titanate, 29.5 parts of strontium titanate, 17.5 parts of titanium dioxide, 12 parts of bismuth oxide, 4 parts of zirconium oxide, 0.3 parts of Nb2O5, 0.7 parts of Y2O3, 1.4 parts of Sb2O3, 1.2 parts of calcium carbonate, 0.15 parts of magnesium oxide, 0.9 parts of cerium dioxide, 0.11 parts of manganese dioxide, 0.4 parts of vanadium pentoxide, 0.1 parts of dysprosium oxide, 5.4 parts of zinc oxide, 3 parts of boric acid, 3 parts of silicon dioxide, 2.4 parts of sodium carbonate, and 0.12 parts of aluminum oxide.

[0034] A method for preparing the high-voltage, low-loss dielectric material described above comprises the following steps: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate, and aluminum oxide are fully mixed, melted at 1200° C. for 1.5 hours, and then water-quenched. Zinc-borosilicate glass powder is obtained by ball milling and granulation, wherein the zinc-borosilicate glass powder has a D50 of less than 0.1 μm. S2. Evenly mix the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide, and dysprosium oxide, and granulate to obtain an oxide powder having a D50 of 0.2 μm. S3. Pressing the oxide powder into tablets at a pressure of 500 MPa, and sintering at 1200° C. for 3 hours to obtain a high-voltage, low-loss dielectric material. Example 3

[0035] A high-voltage, low-loss dielectric material comprises, by mass, 36 parts of barium titanate, 25 parts of strontium titanate, 16 parts of titanium dioxide, 11 parts of bismuth oxide, 3.5 parts of zirconium oxide, 0.28 parts of Nb2O5, 0.6 parts of Y2O3, 1.3 parts of Sb2O3, 1.1 parts of calcium carbonate, 0.14 parts of magnesium oxide, 0.85 parts of cerium dioxide, 0.09 parts of manganese dioxide, 0.35 parts of vanadium pentoxide, 0.09 parts of dysprosium oxide, 4.9 parts of zinc oxide, 2.8 parts of boric acid, 2.9 parts of silicon dioxide, 2.3 parts of sodium carbonate, and 0.11 parts of aluminum oxide.

[0036] A method for preparing the high-voltage, low-loss dielectric material described above comprises the following steps: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate and / or aluminum oxide are fully mixed, melted at 1150° C. for 1.5 h, and then water-quenched. Zinc borosilicate glass powder is obtained by ball milling and granulation, wherein the zinc borosilicate glass powder has a D50 of less than 0.1 μm; S2. Evenly mix the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide and / or dysprosium oxide, and granulate to obtain an oxide powder, wherein the D50 of the oxide powder is 0.15 μm; S3. Pressing the oxide powder into tablets at 450 MPa, and sintering at 1160° C. for 2.5 h to obtain a high-voltage, low-loss dielectric material. Example 4

[0037] A high-voltage, low-loss dielectric material comprises, by mass, 38 parts of barium titanate, 29.5 parts of strontium titanate, 15 parts of titanium dioxide, 9 parts of bismuth oxide, 4 parts of zirconium oxide, 0.24 parts of Nb2O5, 0.7 parts of Y2O3, 1.2 parts of Sb2O3, 1 part of calcium carbonate, 0.13 parts of magnesium oxide, 0.8 parts of cerium dioxide, 0.08 parts of manganese dioxide, 0.3 parts of vanadium pentoxide, 0.08 parts of dysprosium oxide, 4.7 parts of zinc oxide, 2.6 parts of boric acid, 2.6 parts of silicon dioxide, 2.4 parts of sodium carbonate, and 0.12 parts of aluminum oxide.

[0038] A method for preparing the high-voltage, low-loss dielectric material described above comprises the following steps: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate, and aluminum oxide are fully mixed, melted at 1200° C. for 1 hour, and then water-quenched. Zinc borosilicate glass powder is obtained by ball milling and granulation, wherein the zinc borosilicate glass powder has a D50 of less than 0.1 μm; S2. Evenly mix the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide, and dysprosium oxide, and granulate to obtain an oxide powder having a D50 of 0.5 μm. S3. Pressing the oxide powder into tablets at 400 MPa, and sintering at 1200° C. for 2 h to obtain a high-voltage, low-loss dielectric material. Example 5

[0039] A high-voltage, low-loss dielectric material, whose raw materials, calculated by mass, include 35 parts of barium titanate, 20 parts of strontium titanate, 15 parts of titanium dioxide, 11 parts of bismuth oxide, 3 parts of zirconium oxide, 0.24 parts of Nb2O5, 0.56 parts of Y2O3, 1.2 parts of Sb2O3, 1.1 parts of calcium carbonate, 0.14 parts of magnesium oxide, 0.9 parts of cerium dioxide, 0.11 parts of manganese dioxide, 0.4 parts of vanadium pentoxide, 0.1 parts of dysprosium oxide, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of silicon dioxide, 2 parts of sodium carbonate and 0.1 parts of aluminum oxide.

[0040] A method for preparing the high-voltage, low-loss dielectric material described above comprises the following steps: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate, and aluminum oxide are fully mixed, melted at 1100° C. for 1.5 h, and then water-quenched. Zinc borosilicate glass powder is obtained by ball milling and granulation, wherein D50 of the zinc borosilicate glass powder is less than 0.1 μm; S2. Evenly mix the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide, and dysprosium oxide, and granulate to obtain an oxide powder having a D50 of 0.4 μm. S3. Pressing the oxide powder into tablets at 500 MPa, and sintering at 1200° C. for 2 h to obtain a high-voltage, low-loss dielectric material.

[0041] Comparative Example 1 This comparative example is the same as Example 1, except that bismuth oxide is not added in this comparative example.

[0042] Comparative Example 2 This comparative example is the same as Example 1, except that magnesium oxide is not added in this comparative example.

[0043] Comparative Example 3 This comparative example is the same as Example 1, except that in this comparative example, Nb2O5 is replaced by yttrium oxide in equal amounts.

[0044] Comparative Example 4 This comparative example is the same as Example 1, except that Sb2O3 is not added in this comparative example.

[0045] Tablet forming is to uniaxially press the oxide powder into a 12x2mm round piece.

[0046] The withstand voltage strength was tested using a Yangtze 50kV DC power supply, and the dielectric constant, loss, and temperature characteristics were tested using a TH2838 LCR digital bridge in combination with a temperature chamber. The dielectric constant ε of the high-voltage, low-loss dielectric materials in Examples 1-5 and Comparative Examples 1-4 was tested at a frequency of 1kHz. r , dielectric loss tanθ, compressive strength E b The test results are shown in Table 1.

[0047] Group <![CDATA[Dielectric constant ε r > Dielectric loss <![CDATA[Proof strength E b (kV / mm -1 )]]> ∆C / C (-25~85℃) Example 1 2502 0.0003 6.21 <±8% Example 2 2567 0.00035 6.62 <±8% Example 3 2480 0.00038 6.14 <±8% Example 4 2411 0.00031 6.51 <±8% Example 5 2561 0.00032 6.58 <±8% Comparative Example 1 1506 0.00061 5.8 <±10% Comparative Example 2 2411 0.00056 4.2 <±9% Comparative Example 3 1623 0.00065 3.54 <±18% Comparative Example 4 2430 0.0011 4.21 <±18% From the data in the above table, it can be seen that the high-voltage low-loss dielectric material of the present invention has the characteristics of high dielectric constant, low dielectric loss, high compressive strength, etc.

[0048] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A high-voltage, low-loss dielectric material, characterized in that: The raw materials include, by mass, 35-38 parts of barium titanate, 20-29.5 parts of strontium titanate, 15-17.5 parts of titanium dioxide, 9-12 parts of bismuth oxide, 3-4 parts of zirconium oxide, 0.8-1.0 part of X, 1.2-1.4 parts of Sb2O3, 1-1.2 parts of calcium carbonate and / or 0.13-0.15 parts of magnesium oxide, where X is a mixture of Nb2O5 and Y2O3.

2. The high-voltage low-loss dielectric material according to claim 1, characterized in that: The raw materials further include 0.8-0.9 parts of cerium dioxide, 0.08-0.11 parts of manganese dioxide, 0.3-0.4 parts of vanadium pentoxide and / or 0.08-0.1 parts of dysprosium oxide in parts by mass.

3. The high-voltage low-loss dielectric material according to claim 2, characterized in that: The raw materials thereof further include 4.7-5.4 parts of zinc oxide, 2.6-3 parts of boric acid, 2.6-3 parts of silicon dioxide, 2-2.4 parts of sodium carbonate and / or 0.09-0.12 parts of aluminum oxide in parts by mass.

4. The high-voltage low-loss dielectric material according to claim 3, characterized in that: The mass ratio of Nb2O5 and Y2O3 in the X is 3:

7.

5. A method for preparing a high-voltage, low-loss dielectric material according to any one of claims 3, characterized in that: The following steps are included: S1. Calcium carbonate, magnesium oxide, zinc oxide, boric acid, silicon dioxide, sodium carbonate and / or aluminum oxide are melted, quenched with water, and ball-milled to obtain zinc borosilicate glass powder; S2. Evenly mixing the zinc borosilicate glass powder with barium titanate, strontium titanate, titanium dioxide, bismuth oxide, zirconium oxide, X, Sb2O3, cerium dioxide, manganese dioxide, vanadium pentoxide and / or dysprosium oxide, and granulating the mixture to obtain an oxide powder; S3. Pressing the oxide powder into tablets and sintering at 1150° C.-1200° C. to obtain a high-voltage and low-loss dielectric material.

6. The preparation method according to claim 5, characterized in that The melting temperature in S1 is 1100-1200° C., and the melting time is 1-1.5 h.

7. The preparation method according to claim 5, characterized in that The zinc borosilicate glass powder described in S1 has a D50 value less than 0.1 μm.

8. The preparation method according to claim 5, characterized in that The D50 of the oxide powder in S2 is 0.15-0.5 μm.

9. The preparation method according to claim 5, characterized in that The tableting pressure in S3 is 400-500 MPa.

10. Use of the high-voltage, low-loss dielectric material according to any one of claims 1 to 4 in a high-voltage ceramic capacitor.

Citation Information

Patent Citations

  • High performance middle and low temperature sintered high-voltage ceramic capacitor medium

    CN101386534A

  • Doped modified barium titanate-based high-pressure porcelain capacitor material

    CN101759433A

  • Ceramic dielectric formulation for broad band UHF antenna

    EP2492256A2

  • Barium titanate series porcelain composition

    JP1982157502A

  • Semiconductor porcelain composition

    JP1989018213A

Cited By

  • Barium modified sodium borosilicate ltcc substrate and photocuring 3D printing preparation method thereof

    CN122444506A

  • Barium modified sodium borosilicate ltcc substrate and photocuring 3D printing preparation method thereof

    CN122444506B